PREGNANT WOMEN'S KNOWLEDGE ABOUT THE INCIDENT OF MALARIA AND CLEAN, HEALTHY LIVING BEHAVIOR IN AEK MUARA PINANG DISTRICT YEAR 2024 - Friska Apriani Sihombing, (Jurnal Cakrawala Ilmiah, 2024)
Malaria is a tropical disease caused by mosquito bites. This disease can attack all individuals regardless of age and gender and pregnant women are no exception. Malaria in pregnant women has the most severe impact on maternal and fetal morbidity and mortality. One effort to eradicate malaria is clean and healthy living behavior. The research used an analytical survey with a cross sectional approach. The research was conducted in the Aek Muara Pinang sub-district. The population in the study were pregnant women in the Aek Muara Pinang sub-district with a sample of 25 pregnant women respondents. Data analysis used univariate and bivariate with the chi square test. An initial survey conducted by researchers in the Aek Muara Pinang sub-district found that there were still pregnant women experiencing malaria. The results of the research were obtained from 25 respondents, data obtained with good knowledge of 16 (64%) respondents and poor knowledge of 9 (36%) respondents, based on attitudes showed that from 25 respondents data was obtained with good attitudes of 15 (52%) respondents and good attitudes. 10 (48%) respondents were not good, based on Healthy Clean Living Behavior with Malaria Incidents which showed that from 25 respondents data was obtained by implementing good clean and healthy living behavior for 10 (40%) respondents and 15 (60%) respondents with poor healthy clean living behavior. %) respondents. The conclusion of this research is that there is still a lack of knowledge among pregnant women about the dangers of malaria during pregnancy and a lack of clean living behavior in preventing malaria